2018
DOI: 10.3390/su10093062
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perception of Water Quality and Risks in the Mashavera River Basin, Georgia: Analyzing the Vulnerability of the Social-Ecological System through Community Perceptions

Abstract: Competing natural resources usage that leads to dramatic land use changes can threaten the balance of a social-ecological system. When this is the case, communities are directly exposed to the negative consequences of those land use changes. The Mashavera River Basin is considered one of the hotspots of environmental pollution in Georgia. This is of importance for public health because the food production from this basin meets a substantial proportion of the country’s food demand. The farmers’ perception of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 89 publications
0
29
0
2
Order By: Relevance
“…Furthermore, it is interesting to note that most published studies reported above have taken place prior to planning an intervention, which is the case especially in water-related studies. These public risk assessments of water quality are equally as important as the experts' technical assessments to ensure complementary decisions that organise the responses to degradation, implement risk management policies, minimise risks and allocate resources [11,29,50]. Understanding the way a particular society perceives risk is vital for pinpointing the existing vulnerabilities of a water-related occurrence, and appraisals of environmental risks that include all stakeholders are an integral part of promoting environmental sustainability [51].…”
Section: Risk Research In the Water Sectormentioning
confidence: 99%
“…Furthermore, it is interesting to note that most published studies reported above have taken place prior to planning an intervention, which is the case especially in water-related studies. These public risk assessments of water quality are equally as important as the experts' technical assessments to ensure complementary decisions that organise the responses to degradation, implement risk management policies, minimise risks and allocate resources [11,29,50]. Understanding the way a particular society perceives risk is vital for pinpointing the existing vulnerabilities of a water-related occurrence, and appraisals of environmental risks that include all stakeholders are an integral part of promoting environmental sustainability [51].…”
Section: Risk Research In the Water Sectormentioning
confidence: 99%
“…Farmers' perceptions of the importance of stewardship of water quality are increasing globally [32][33][34]. This is important for the achievement of both local enhancement of water quality (farm scale) and for downstream water users, and was an important driver of the research described here.…”
Section: Other Management Considerationsmentioning
confidence: 96%
“…Like any qualitative research, the limited number of interview participants does not allow for exploring data across various dimensions (e.g., socio-demographics). Past studies report that stakeholders' knowledge of an environmental problem, personal experience (e.g., Tarannum, Kansal, & Sharma, 2018), social position and regulatory roles (e.g., Haeffner, Jackson-Smith, & Flint, 2018), and socio-demographic characteristics (Fobil, May, & Kraemer, 2010;Haeffner et al, 2018;Withanachchi et al, 2018) may affect their evaluation of an environmental resource and their motivations to support interventions. Therefore, future studies could benefit from a stratified sampling strategy where participants are recruited based on various sociodemographic characteristics such as type of economic activity (e.g., farmers and industrialists) and income classes.…”
Section: Support Communal Initiativesmentioning
confidence: 99%